2005
DOI: 10.2527/2005.8392175x
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental safflower oil affects the fatty acid profile, including conjugated linoleic acid, of lamb

Abstract: The objective of this study was to determine whether increasing levels of dietary safflower oil would alter unsaturated fat (especially CLA) and tocopherol content of lamb, animal performance, carcass characteristics, or color stability of lamb muscle tissue. Targhee x Rambouillet wethers (n = 60) were assigned to one of three diets (four pens per treatment with five lambs per pen) in a completely random design. Diets were formulated with supplemental safflower oil at 0 (control), 3, or 6% (as-fed basis) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
32
2
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 20 publications
13
32
2
8
Order By: Relevance
“…C18:1 is the most abundant fatty acid which is in agreement with other studies (Kott et al, 2003;Boles et al, 2005;Juarez et al, 2008). Significant influence of the dietary treatment on C18:1 was observed in subcutaneous and omental fat showing highest content in the group fed rapeseed meal and lowest in the DDGS group.…”
Section: Saturated and Monounsaturated Fatty Acidssupporting
confidence: 80%
“…C18:1 is the most abundant fatty acid which is in agreement with other studies (Kott et al, 2003;Boles et al, 2005;Juarez et al, 2008). Significant influence of the dietary treatment on C18:1 was observed in subcutaneous and omental fat showing highest content in the group fed rapeseed meal and lowest in the DDGS group.…”
Section: Saturated and Monounsaturated Fatty Acidssupporting
confidence: 80%
“…As previously reported (Boles, Kott, Hatfield, Bergman, & Flynn, 2005;Kott et al, 2003), 18:1n−9 was the most abundant adipose tissue fatty acid. Weight percentages of fatty acids were similar (P N 0.16) between lambs fed control and 0JUN diets except that lambs fed the control diet had greater (P b 0.05) weight percentages of 14:0, 18:1trans−6 and trans−10 isomers, total 18:1trans isomers, and percentage of SFA (not including 18:0) than lambs fed 0JUN and tended to have greater (0JUN, 33JUN, 66JUN, and 100JUN).…”
Section: Adipose Tissue Fatty Acid Compositionsupporting
confidence: 64%
“…Researchers have demonstrated that dietary alterations of both ruminant and non-ruminant animals could increase the unsaturated fatty acid and CLA levels of meat, thereby improve its potential health benefits (Boles et al, 2005). The only plausible way to increase muscle CLA content effectively would be to provide chemically synthesized CLA as a dietary supplement in pigs (Joo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%